RETRACTED: Alrubaiq, A.; Alharbi, T. Developing a Cybersecurity Framework for e-Government Project in the Kingdom of Saudi Arabia. J. Cybersecur. Priv. 2021, 1, 302–318 - Abdullah Alrubaiq; Talal Alharbi (Journal of Cybersecurity and Privacy)
The journal retracts the article titled “Developing a Cybersecurity Framework for e-Government Project in the Kingdom of Saudi Arabia” [...]